Effect of Core Stability Training on Unstable Support Surfaces in Postoperative Rehabilitation of Thoracolumbar Vertebral Compression Fractures in the Elderly - Yin, Yanfei; Cao, Shixia; Wang, Chenjie; Liu, Yanju; Zhang, Huakai (Computational and mathematical methods in medicine, 2022)
Objective. Thoracolumbar vertebral compression fractures (TVCF) are caused by anterior flexion or vertical downward violence to the spine (Sezer et al. 2021). This study is aimed at investigating the effect of core stability training (CST) on unstable support surfaces in the postoperative rehabilitation of TVCF in the elderly. Methods. Ninety-eight patients with TVCF who underwent surgical treatment in our hospital from July 2021 to April 2022 were selected as study subjects. Then, they were divided into a research group receiving unstable support surface CST and a control group with conventional rehabilitation training according to the random number table method. Before and after the training, the X-ray machine was positioned and the anterior margin and middle height ratio and the posterior convex Cobb angle of the injured vertebrae were observed, and the balance detector was used to detect patients’ eye opening and closing trajectory length, Romberg rate, and to perform gait test. Patients’ pain, lumbar spine function, and quality of life were subsequently assessed using the Visual Analogue Scale (VAS), Oswestry Dysfunction Index (ODI), Generic Quality of Life Inventory-74 (GQOL-74), and patient satisfaction with rehabilitation was investigated. Results. After rehabilitation training, there was no statistically marked difference in eye-opening trajectory length between both groups (P>0.05). The research group had higher scores than the control group in all dimensions of the anterior border of the injured vertebra, middle height ratio, and GQOL-74, while the posterior convex Cobb angle, closed-eye trajectory length, Romberg rate, VAS, and ODI were lower than the control group (P<0.05). The research group also revealed better gait improvement and higher rehabilitation satisfaction than the control group after training (P<0.05). Conclusion. Unstable support surface CST can effectively improve postoperative vertebral body rehabilitation, balance function, gait, pain conditions, and lumbar spine function in elderly TVCF patients, and enhance their quality of life and rehabilitation satisfaction. This trial is registered with ChiCTR2000014547.